Cerâmica medieval das escavações no Castelo de Arouca : ensaio de análise morfotipológica - Silva, António Manuel S.P.; Silva, Manuela C.S. (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The paper presents the first results of a study which is being carried on with an assemblage of medieval ceramic sherds proceeding from 1994-96 digs at Valinhas’ castle, Arouca. Aspects related to pots’ forms and decorations are discussed, and a preliminary account describes several forms such as jars, storage pots, jugs, bowls, and dishes of different sizes. A chronology between 9th-10th and the 12th centuries is proposed for these ceramics.